Insights into the Fluoride Ions Response Mechanism for the Novel 2,2’:6’,2’’-Terpyridine Fluorescent Sensor (Journal of Atomic and Molecular Sciences, 2018)
In this present work, the sensing mechanism of a novel fluoride chemosensor 2,2':6',2''-terpyridine(abbreviated as “2” according to previous experiment) has been investigated based on density functionaltheory (DFT) and time-dependent DFT (TDDFT) methods. The theoretical electronic spectra (verticalexcitation energies and fluorescence peak) reproduced previous experimental results [RSC Adv. 2014, 4,4041.], which confirms the rationality of our theoretical level used in this work. The constructed potentialenergy curve suggest that the non-barrier process could be responsible for the rapid response to fluorideanion. Analyses about binding energies demonstrate that only fluoride anion could be detected for 2chemosensor in acetonitrile solvent. Comparing with other anions, we confirm the uniqueness of fluorideanion for 2 sensor. In view of the excitation process, the strong intramolecular charge transfer (ICT) processof $S_0→ S_1$ transition explain the redshift of absorption peak for 2 sensor with the addition of fluoride anion.This work not only presents a straightforward sensing mechanism of fluoride anion for 2 chemosensor, butalso plays important roles in synthesizing and designing fluorescent sensors in future.